A new strikingly-colored species of the genus Galathea Fabricius, 1793 (Crustacea: Decapoda: Anomura: Galatheidae) from the Ryukyu Islands, Japan - Osawa, Masayuki (Zootaxa, 2015)
A new shallow-water squat lobster, Galathea ryuguu, is described on the basis of material obtained from a colony of unidentified sea fan of the genus Muricella Verrill, 1868. The new species is most closely allied to G. squamea Baba, 1979, but is distinguished by the ornamentation and armature of the carapace, third maxilliped, and ambulatory legs.